Capacitação de mães de bebês pré-termo como agentes de promoção do desenvolvimento, no ambiente hospitalar - Joaquim, Regina Helena Vitale Torkomian (2008)
This research aimed to produce (enhance) the knowledge on the necessities and possibilities for the qualification of the mother of preterm baby to work as development improver agent during the hospital internment of this babies. The research was conducted through two articulated studies , implemented in a hospital institution, having as participants the mothers (or equivalents) with interned babies and the professionals who worked on the External Nursery, where the babies stay waiting for the medical advice after the Neonatal Intensive Care Unit (NICU). The # 1 Study corresponds to the examination of the process of procedures elaboration for a teaching program to the mothers or baby sitter during the baby stay in the NICU which included the development of skills of the mothers of preterm babies to care them during their stay in the NICU, considering the needs and peculiarities of this situation. The #1 Study also searched the identification of the procedures used by the professionals to prepare the mother in that sense, by mean of interviews and observation (direct and through video taping) of situation of mother and baby interaction and mother and professional interaction; and the proposition of the objective and teaching conditions compatible with such necessities and available resources. From this #1 Study resulted a modular teaching program, with corresponding unit of relevant abilities and, related to that, a set of information, demonstration and training exercises. In the #2 Study, which corresponds to the evaluation of the teaching resources, proposed as conditions for the mother training; from the implemented program units starting point, with a group of mothers of preterm babies, during their stay in the hospital environment after leaving the neonatal intensive care unit, information was gathered that could indicate the efficiency of the program to promote such abilities, at least on the spoken feed back level of the participant mothers. For that, direct observation of the action of the mothers (before, during and after the implementation of the teaching modules which each one was submitted) and interviews (before and after the teaching activities). Such observations indicated a possible impact of the implemented activities due to the revealing changes on the spoken report and even in the manner of the mother in interacting with the baby, and also provided a better understanding on the conditions that favor or not the training of the mother to care their baby, regarding the routine and characteristics of the situation on the transition of the baby from the neonatal intensive care unit to their home.